Multilateral Debt Relief Initiative : A First Assessment of Eligible Countries. (Policy Papers; Policy Paper ;, 2005)
This paper responds to the Board's request for an assessment of eligible countries that could qualify for Fund debt relief under the MDRI once the requisite consents and requests have been received. Directors requested that, by end-2005, staff prepare, in collaboration with the World Bank, an assessment of the 18 post-completion point HIPCs, as well as eligible non-HIPCs, and propose for Board consideration a list of members that would qualify immediately for MDRI debt relief. Directors also requested that, for those members that do not presently meet the MDRI qualification criteria, remedial measures be expressly identified that would allow them to qualify for MDRI relief.